Prioritizing Women’s Heart Health: An Urgent Call to Action - Gajurel, Ratna Mani (Nepalese Heart Journal, 2024)
Heart disease is often mistakenly perceived as a predominantly male issue, but the reality tells a different story. Women are equally susceptible to heart-related illnesses, yet they face unique challenges that often go unrecognized.1`This editorial shed light on the critical need to prioritize women’s heart health and calls for urgent action to address the disparities and gaps in care that persist.....